Відповідь:
6x(x^2 - 4) = 0, so the solutions are x = 0, x = 2, and x = -2.
x(25x^2 - 10x + 1) = 0, using the quadratic formula, we can find that the solutions are x = 0, x = (2 + sqrt(3))/5, and x = (2 - sqrt(3))/5.
(x^2 - 9)(x - 4) = 0, so the solutions are x = -3, x = 3, and x = 4.
Пояснення:
Ответ:
1)6x^3-24x=0
6x*(x^2-4)=0
x*(x^2-4)=0
x1=0
x^2-4=0
x1=(-2),x2=0,x3=2
2)25x^3-10x^2+x=0
x*(25x^2-10x+1)=0
x*(5x-1)^2=0
x=0
(5x-1)^2=0
x1=0,x2=1/5
3)x^3-4x^2-9x+36=0
x^2*(x-4)-9(x-4)=0
(x-4)*(x^2-9)=0
x-4=0
x2-9=0
x1=(-3),x2=3,x3=4
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Відповідь:
6x(x^2 - 4) = 0, so the solutions are x = 0, x = 2, and x = -2.
x(25x^2 - 10x + 1) = 0, using the quadratic formula, we can find that the solutions are x = 0, x = (2 + sqrt(3))/5, and x = (2 - sqrt(3))/5.
(x^2 - 9)(x - 4) = 0, so the solutions are x = -3, x = 3, and x = 4.
Пояснення:
Ответ:
1)6x^3-24x=0
6x*(x^2-4)=0
x*(x^2-4)=0
x1=0
x^2-4=0
x1=(-2),x2=0,x3=2
2)25x^3-10x^2+x=0
x*(25x^2-10x+1)=0
x*(5x-1)^2=0
x=0
(5x-1)^2=0
x1=0,x2=1/5
3)x^3-4x^2-9x+36=0
x^2*(x-4)-9(x-4)=0
(x-4)*(x^2-9)=0
x-4=0
x2-9=0
x1=(-3),x2=3,x3=4